Factors associated with prevalence of oral lesions and oral self-examination in young adults from a birth cohort in Southern Brazil - Sandra Beatriz Chaves Tarquinio; Luisa Jardim Correa de Oliveira; Marcos Britto Correa; Marco Aurélio Peres; Karen Glazer Peres; Denise Petrucci Gigante; Bernardo Lessa Horta; Flávio Fernando Demarco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The objective of this study was to assess the prevalence and characteristics of oral lesions and oral self-examination and the association between these variables and life course determinants in a young population. A representative sample (n = 720) of all births occurring in Pelotas, Rio Grande do Sul State, Brazil, in 1982, was investigated and the outcomes were assessed in 2006. Data regarding exploratory variables was collected from other cohort waves. The prevalence of oral lesions was 23.3% (95%CI: 20.3-26.6). A total of 31% of individuals (95%CI: 27.6-34.4) reported never having performed oral self-examination. Multivariable analysis showed that low socio-economic status at birth, lack of oral hygiene instruction from a dentist up to the age of 15 years and smoking habits at the age of 22 year were associated with the presence of oral lesions. Performing oral self-examination was associated with high levels of maternal schooling at birth and having received oral hygiene orientation from a dentist up to the age of 15 years. Socioeconomic and behavioral factors are associated with both presence of oral mucosal lesions and the habit of performing self-examination.